PENGARUH KOMBINASI CACING DARAH (Chironomus sp.) DAN PAKAN KOMERSIAL TERHADAP PERTUMBUHAN SERTA KELANGSUNGAN HIDUP IKAN PATIN (Pangasius hypophthalmus) - Andreana Avelina; Priyo Santoso; Agnette Tjendanawangi (Jurnal Aquatik, 2026)
Feed is a crucial factor in fish farming. Without appropriate feed, fish growth slows down, and survival rates can decline. High commercial feed costs often pose a challenge. Consequently, many fish farmers seek highly nutritious alternatives; bloodworms (Chironomus sp.) are a promising option due to their protein content, which supports fish growth. This study examined the effects of combining bloodworms with commercial feed on the growth and survival of Pangasius hypophthalmus (Siamese catfish). The experiment was conducted over 60 days at the Aquaculture Laboratory of Nusa Cendana University, Kupang, using a Completely Randomized Design (CRD). Four treatments were tested—control (100% pellets), Treatment A (85% pellets + 15% bloodworms), Treatment B (70% pellets + 30% bloodworms), and Treatment C (55% pellets + 45% bloodworms)—with three replicates for each. The results clearly indicated that the combination of commercial feed and bloodworms significantly influenced the growth of P. hypophthalmus (p<0.05). Treatment C (45% bloodworms) yielded the best growth performance, achieving an absolute weight gain of 2.73 g and a specific growth rate (SGR) of 1.27% per day. However, regarding survival, Treatment B performed best, achieving a rate of 86.66%. Water quality remained stable throughout the study, with temperatures ranging from 26–30°C and pH levels between 6.2–8.3—ranges ideal for P. hypophthalmus. The study concludes that incorporating bloodworms at a proportion of up to 45% alongside commercial feed can accelerate the growth of P. hypophthalmus without compromising survival rates. Keywords: Bloodworms, Catfish, Survival, Commercial Feed, Growth